WHEN SCHOOLS BECOME PRISONS (ANALYSIS OF THE REALITY OF THE SOCIAL TRAGEDY OF INDONESIAN EDUCATIONAL SYSTEM PRODUCTS) - Fuad Mardhatillah (CV Naskah Aceh, 2022)
The massive social and humanitarian disasters and tragedies currently occurring in this country are a consequence of the failure of the social function of school institutions in educating the spiritual substance of humanity. So far, school has been run as a teaching vehicle that focuses more on and emphasizes the issues of mastering scientific information, the formation of skills, expertise and professionalism that are dry of human values. Meanwhile, the spiritual dimension of humans, which is more directed towards the formation of social awareness and sensitivity, is overlooked by school institutions, as something that is most essential in the educational process in schools. This can happen after educational stakeholders have both been absorbed by the spirit and life orientation of pragmatism-materialism. So that interpersonal relationships between school alumni and members of the wider community who live around them become counter-productive, oppressive, subjugating and even tend to prey on each other (vulture culture). So social disasters and tragedies spread in various variants. School institutions should be understood as social institutions, where all educational processes that take place within them must adhere firmly to basic human principles and values ​​which are autonomous, relative, unique, dynamic and free/independent and responsible. The logical consequence is that students must be placed as subjects who have the right to freedom of self-actualization and choose their future correctly, intelligently, independently and responsibly. Teachers only function as motivators, facilitators and moderators who provide them with various information that can awaken the students' human souls. So that in the end, school alumni do not just have physical and physical abilities and skills for the five senses, but the human side in the context of understanding